ANALISIS PASAL 39 AYAT 3 KHI TENTANG LARANGAN KAWIN KARENA SESUSUAN: PERSPEKTIF FILSAFAT HUKUM ISLAM - Armita, Pipin (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2016)
The Compilation of Islamic Law (KHI) cannot be separated from the rules of law written in the Qur'an and Hadith. Article 39 paragraph 3 of The Compilation of Islamic Law (KHI) states that there is a prohibition on marriage due to the same breastfeeding mother. Philosophically, Allah's purpose in prescribing the law is to preserve the benefits of human beings, as well as to avoid ‘mafsadat’, both in the world and in the hereafter. In article 39 paragraph 3 KHI, the determination of the law is in order to realize the benefits of human beings. There are five main elements that are protected against the law of prohibition on marriage due to the same breastfeeding mother as mentioned in article 39 paragraph 3 KHI. The five main elements are religion (ḥifẓ ad-dīn), soul (ḥifẓ an-nafs), reason (ḥifẓ al-‘aql), descendants (ḥifẓ an-nasl), and property (ḥifẓ al-māl).[Kompilasi Hukum Islam (KHI) tidak lepas dari kaidah-kaidah hukum yang tertulis dalam al-Qur’an dan Hadis. Pasal 39 ayat 3 Kompilasi Hukum Islam (KHI) menyatakan adanya larangan melangsungkan perkawinan karena sesusuan. Secara filosofis, tujuan Allah mensyariatkan hukumnya adalah untuk memelihara kemaslahatan manusia, sekaligus untuk menghindari mafsadat, baik di dunia maupun di akhirat. Dalam pasal 39 ayat 3 KHI, penetapan hukum tersebut dalam rangka mewujudkan kemaslahatan manusia. Ada lima unsur pokok yang dilindungi terhadap penetapan hukum keharaman menikah karena sesusuan yang tercantum dalam pasal 39 ayat 3 KHI. Kelima unsur pokok tersebut adalah agama (ḥifẓ ad-dīn), jiwa (ḥifẓ an-nafs), akal (ḥifẓ al-‘aql), keturunan (ḥifẓ an-nasl), dan harta (ḥifẓ al-māl).]